The effect of Taxes on the wireless telecommunications sector in Jordan during the period (2011-2015) - Alhajeid, Hassan Nabil; Alhajeid, Sana Salim (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aimed at a general preliminary discussion of the implications of taxes on communications services and public taxes such as VAT on goods and services or all. This research follows the descriptive method, which collects information from its various sources and submits it to Therefore, the researcher will study the literature related to the study and a number of published and unpublished sources, such as the working papers of conferences, workshops, seminars, articles, in addition to previous studies and researches. He will also work on studying statistics and publications issued by ministries and public research centers. The study's hypothesis provided that there is an inverse relationship between the taxation of the telecommunications sector and the sector's contribution to GDP.The study's hypothesis provided that there is an inverse relationship between the taxation of the telecommunications sector and the sector's contribution to GDP.The research concludes with several results that can be summed up in five points:1_Annual profit declined by 5.7 in the first half of the year: 2015 compared with 2014. Consumer spending fell by 18% in the year: 2012, compared to 2011.2-The decline in the number of employees in the sector by 441 employees between years: 2011 and 2015 AD.3- The sector's participation in GDP fell from 8.96% in 2010 to 5.67% in 2014.The study's thesis_ which states that there is an inverse relationship between the taxation of the telecommunications sector and the sector's contribution to GDP - is well established.
Keywords: taxes; sales tax; service production sectors; public finance; fiscal policy; gross national product